1996
DOI: 10.1046/j.1365-2249.1996.25732.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of HIV-1 replication following influenza vaccination of HIV+ individuals

Abstract: Levels of HIV‐1 have been reported to increase in peripheral blood after influenza vaccination of HIV+ individuals. In this study we have evaluated the dynamics of these changes. Ten HIV‐1+ individuals classified in revised CDC clinical categories B and C as well as five seronegative healthy controls were vaccinated with the recommended influenza strains. HIV viral RNA and proviral DNA were sequentially quantified in serum and blood lymphocytes, respectively. Nine of the 10 HIV+ individuals had an increase in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 18 publications
3
21
0
4
Order By: Relevance
“…18 The antibody response was evaluated according to the parameters set out by the European Medicines Evaluation Agency (EMEA) for subjects aged between 18 and 60 years and comprising a geometric mean titre (GMT) T 30 /T 0 ratio ≥ 2.5, seroconversion ≥ 40%, and postvaccine seroprotection ≥ 70%. 19 Seroconversion was defined as the onset of a titre in negative subjects or an increase of at least four-fold in the antibody titre between T 0 and T 30 . Seroprotection was defined as an antibody titre ≥ 1:40.…”
Section: Immunogenicitymentioning
confidence: 99%
See 2 more Smart Citations
“…18 The antibody response was evaluated according to the parameters set out by the European Medicines Evaluation Agency (EMEA) for subjects aged between 18 and 60 years and comprising a geometric mean titre (GMT) T 30 /T 0 ratio ≥ 2.5, seroconversion ≥ 40%, and postvaccine seroprotection ≥ 70%. 19 Seroconversion was defined as the onset of a titre in negative subjects or an increase of at least four-fold in the antibody titre between T 0 and T 30 . Seroprotection was defined as an antibody titre ≥ 1:40.…”
Section: Immunogenicitymentioning
confidence: 99%
“…Mean lymphocyte counts before vaccination (T 0 ), at 30 days (T 30 ) and 180 days (T 180 ) after immunization, divided according to the classification categories defined by the CDC, are shown in Table 2. Between-group comparisons of the lymphocyte counts at different observation times (T 0 versus T 30 and T 0 versus T 180 ) failed to reveal any statistically significant changes, with the exception of subjects with lymphocyte counts < 200 cells/mm 3 , vaccinated with conventional subunit vaccine, whose counts showed a progressive increase after immunization (P = 0.048).…”
Section: Cd4+ T-lymphocyte Countmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients infected with flu virus, viral replication is occurring on the mucosal surface of respiratory tracts and virions are also found in mucosa-associated lymphoid tissue that is also one of the natural reservoir of HIV-1 (32-34), therefore suggesting the possible co-localization of both pathogens at the same site. Although previous studies have indicated that influenza vaccination could increase HIV-1 viral loads (35,36), a recent study has indicated that influenza infection did not alter HIV-1 viral load or the rate of CD4ϩ T cell decline or clinical progression (37). However, no study has directly addressed the role of flu-derived NA on the HIV-1 replicative cycle.…”
mentioning
confidence: 99%
“…A vacinação por agentes que possuem antígenos dependentes do linfócito T, como é o caso da vacina contra a influenza com vírus inativados, pode levar, teoricamente, a um aumento na replicação do HIV, com infecção de novas células, resultando em uma maior destruição celular, podendo, por isso, ser até prejudicial ao organismo [7][8][9] .…”
unclassified